Preparation method of carbon fiber knife rest and carbon fiber knife rest
By adopting modified carbon fiber prepreg, multifunctional nanofiber reinforced layer, low-temperature performance optimized nanocomposite coating and special hot press forming process in the carbon fiber tool holder, the problem of easy brittleness and insufficient grip in the low temperature environment is solved, and high strength, lightweight and excellent low-temperature performance is achieved.
Patent Information
- Application Number
- CN202510035414.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
AI Technical Summary
The existing carbon fiber knife holders are prone to become brittle in low temperature environments, lack of grip, and complex manufacturing processes, resulting in poor consistency and difficulty in balancing lightweight and high strength.
Modified carbon fiber prepreg, multifunctional nanofiber reinforced layer, low-temperature performance optimized nanocomposite coating and special hot press forming process are adopted to improve the toughness and strength of the tool holder through the synergistic effect of nano toughening agent and multifunctional nanofiber reinforced layer, and improve grip through low-temperature performance optimization of nanocomposite coating.
It significantly improves the mechanical properties and toughness of the tool holder in extremely low temperature environments, extends fatigue life, enhances ice grip, and achieves a perfect combination of lightweight and high strength.
Smart Images

Figure CN119898047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber tool holders, and in particular to a preparation method of a carbon fiber tool holder and a carbon fiber tool holder. Background Art
[0002] The research and development of carbon fiber tool holders has always been a hot topic in the field of ice sports equipment. With the continuous improvement of competitive level, athletes have increasingly stringent performance requirements for tool holders. Although the traditional metal tool holders have mature technology, it has been difficult to make breakthroughs in terms of lightweight and performance optimization. In recent years, carbon fiber composite materials have gradually become the preferred material for high-performance tool holders due to their excellent specific strength and specific modulus. However, the existing carbon fiber tool holders still have some problems that need to be solved.
[0003] First, carbon fiber composite materials tend to become brittle in low-temperature environments, which affects the service life and safety of the blade holder on the ice. Especially in high-intensity training and competitions, the blade holder may produce microcracks due to repeated impact and bending, which may eventually lead to catastrophic accidents. Secondly, the ice grip of carbon fiber blade holders has always been a problem. Although there are some surface treatment technologies, maintaining good grip while also taking into account wear resistance and stability places extremely high demands on material design. Furthermore, the manufacturing process of carbon fiber blade holders is complex and quality control is difficult, resulting in poor product consistency and large performance fluctuations. Finally, it is difficult for existing carbon fiber blade holders to achieve a perfect balance between light weight and high strength, which limits athletes from performing at their best in competitions. Summary of the invention
[0004] The present invention aims at the above problems and proposes an innovative method for preparing a carbon fiber tool holder. The method achieves a comprehensive improvement in the performance of the carbon fiber tool holder through multiple innovations.
[0005] The object of the present invention is to provide a method for preparing a carbon fiber tool holder, comprising the following steps: (1) preparing a modified carbon fiber prepreg, including preparing a resin system, dispersing a nano toughening agent, and impregnating the carbon fiber; (2) preparing a multifunctional nanofiber reinforcement layer, including preparing a spinning solution, electrospinning, post-treatment of the nanofiber web, and carbonization treatment; (3) toolholder forming, including mold preparation, layup, and hot press forming; (4) Surface treatment; (5) Applying low temperature performance optimized nanocomposite coatings, including preparation of coating materials, coating and curing; Wherein, the carbon fiber content in the modified carbon fiber prepreg is 60-70 parts by weight, and the resin content is 30-40 parts by weight.
[0006] Specifically, the preparation of the resin system in step (1) specifically includes: Stir 25-30 parts by weight of tetrafunctional epoxy resin and 5-8 parts by weight of hydroxyl-terminated polyether epoxy resin at 65-70°C for 30 minutes at a speed of 200-250rpm; cool to 50-55°C, add 15-18 parts by weight of 4,4'-diaminodiphenyl sulfone, and stir for 20 minutes; then add 0.3-0.5 parts by weight of triphenylphosphine, and stir for 10 minutes; degas for 15 minutes under a vacuum of 0.05-0.1MPa.
[0007] Specifically, the step (1) of dispersing the nano toughening agent specifically includes: 0.5-1.0 parts by weight of graphene nanosheets and 2-3 parts by weight of core-shell structured nano rubber particles were added to the resin system, and dispersed using a three-roll mill with roller gaps of 20 μm, 10 μm and 5 μm, respectively, and ground three times, each time for 10 minutes.
[0008] Specifically, the carbon fiber impregnation in step (1) specifically includes: 62-67 parts by weight of T800H grade carbon fiber are impregnated by hot melt method at 85-90°C at a speed of 2.5-3.5m / min, and the resin content is controlled to be 33-37wt% and the volatile content is ≤0.3wt%.
[0009] Specifically, the step (2) comprises: a) preparing a spinning solution: stirring polyacrylonitrile cellulose precursor, polyetheretherketone and N,N-dimethylformamide at a weight ratio of 13:2:85 at 60° C. for 24 hours at a speed of 150 rpm, and then ultrasonically treating for 30 minutes (power 300 W, frequency 40 kHz); b) Electrospinning: Electrospinning was performed at 22-25°C, 45-55% relative humidity, using a voltage of 16-19 kV, a propulsion rate of 0.8-1.2 mL / h, a collection distance of 18-22 cm, and a collector speed of 1000-1200 rpm; c) Post-treatment of the nanofiber web: drying in a vacuum oven at 80 °C for 4 h; d) Carbonization treatment: first, heat to 265-275°C at a rate of 1.5°C / min in air, hold for 2.5 hours, then cool to room temperature at a rate of 2°C / min; then heat to 900-950°C at a rate of 8°C / min in a nitrogen atmosphere (purity 99.999%), hold for 1.5 hours, and finally cool to room temperature at a rate of 5°C / min.
[0010] Specifically, the step (3) comprises: a) Mold preparation: Use a high-temperature alloy steel mold with a chrome-plated surface, with a surface roughness of Ra ≤ 0.2μm, and coat it with a nano-ceramic-based release agent; b) Laying: Lay the prepreg in the order of [0° / 90° / +45° / -45°]s 8 layers of bottom layer, [0° / ±30° / 90°]s 6 layers of middle layer, [0° / ±15°]s 6 layers of top layer, and add a multifunctional nanofiber reinforcement layer between the 4th and 16th layers; c) Hot pressing: first pre-treat under vacuum of ≤0.05MPa for 45 minutes; then heat and cure in three stages: increase to 110-115℃ at a rate of 3℃ / min and hold for 70 minutes, then increase to 155-160℃ at a rate of 2℃ / min and hold for 90 minutes, and finally increase to 180-185℃ at a rate of 1℃ / min and hold for 60 minutes; the pressure is controlled to gradually increase to 2MPa from 0-70 minutes, maintain 2MPa from 70-160 minutes, increase to 5MPa from 160-220 minutes and maintain until cooling; when cooling, reduce to 60℃ at a rate of 2℃ / min, and then cool naturally to room temperature.
[0011] Specifically, the step (4) comprises: Use oxygen / argon mixed plasma (ratio 4:1), at a working pressure of 20-30Pa, a power of 250-300W, and process for 45-60 seconds.
[0012] Specifically, the step (5) comprises: a) preparing the coating material: dissolving 75-80 parts by weight of polyvinylidene fluoride in 180-200 parts by weight of N-methylpyrrolidone, stirring at 60° C. for 2 hours; adding 8-10 parts by weight of boron nitride nanosheets and 1-2 parts by weight of graphene quantum dots, and ultrasonically dispersing for 30 minutes (power 400 W, frequency 40 kHz); grinding using a planetary ball mill for 12 hours at a speed of 300 rpm; b) Coating: Use electrostatic spraying method, spraying voltage 50-60kV, spraying thickness 25-35μm; c) Curing: Pre-dry at 60°C for 30 minutes, then cure at 180°C for 45 minutes and cool naturally to room temperature.
[0013] The carbon fiber tool holder is prepared by the preparation method.
[0014] Specifically, the tool holder also includes a metal connector, which is bonded to the tool holder via a modified epoxy adhesive, wherein the shear strength of the modified epoxy adhesive is ≥30MPa and the curing condition is 3 hours at 80°C; the width of the middle connecting part of the tool holder is 3-5mm.
[0015] The innovative features and technical effects of the present invention are mainly reflected in the following aspects: First, the present invention introduces a nano toughening agent system. By cleverly combining graphene nanosheets and core-shell structured nano rubber particles, the microstructure of the composite material is improved at the molecular level. Graphene nanosheets, with their unique two-dimensional structure and excellent mechanical properties, form an efficient stress transfer network in the matrix. When the material is subjected to external force, this network can quickly disperse the stress and prevent the initiation of cracks caused by stress concentration. At the same time, the core-shell structured nano rubber particles maintain good elasticity at low temperatures, can absorb impact energy, and further improve the toughness of the material. The synergistic effect of these two nano materials enables the tool holder to maintain excellent mechanical properties even in extremely low temperature environments.
[0016] Secondly, the present invention develops a multifunctional nanofiber reinforcement layer. The PAN / PEEK nanofiber mesh prepared by electrospinning technology forms a reinforcement network with a unique structure after a special carbonization treatment. This network not only improves the overall strength and rigidity of the tool holder, but also significantly improves the interlayer bonding force. The PAN-based carbon nanofiber provides excellent mechanical properties, while the PEEK component gives the network good toughness and fatigue resistance. The introduction of this multifunctional reinforcement layer effectively solves the problem of interlayer peeling that is prone to occur in traditional carbon fiber tool holders.
[0017] Furthermore, the present invention adopts an innovative hot pressing molding process. Through a carefully designed multi-stage heating and curing process, sufficient flow of resin and complete impregnation of fibers are achieved, while minimizing the generation of internal stress. This process not only improves the consistency of the product, but also significantly extends the fatigue life of the tool holder. Especially in the use environment of repeated bending and impact, this optimized internal structure can effectively prevent the initiation and expansion of microcracks.
[0018] In addition, the present invention has developed a nanocomposite coating with optimized low-temperature performance. With PVDF as the matrix, boron nitride nanosheets and graphene quantum dots are added to form a multifunctional surface protection layer. PVDF itself has excellent low-temperature performance and chemical stability, while the boron nitride nanosheets greatly improve the wear resistance and thermal conductivity of the coating. More importantly, the graphene quantum dots form a nanoscale rough structure on the surface of the coating, which can produce more microscopic melting points on the ice surface, thereby significantly improving the grip of the tool holder.
[0019] Finally, the present invention achieves a perfect combination of lightness and high strength by selecting high-performance T800H grade carbon fiber and optimizing the fiber content. The ultra-high strength and modulus of T800H fiber, combined with the carefully designed fiber arrangement, enable the tool holder to maintain its lightness while having mechanical properties sufficient to cope with extreme sports.
[0020] Through the above innovations, the present invention successfully solves many technical problems faced by existing carbon fiber tool holders. Experimental results show that the tool holder prepared by the present invention exhibits excellent mechanical properties and toughness in low temperature environments, significantly improves fatigue life, significantly enhances ice grip, and achieves a higher strength-to-weight ratio. These comprehensive performance improvements provide a solid equipment foundation for ice athletes to pursue extreme performance.
[0021] In general, the present invention has achieved breakthrough progress in material design, structural optimization and manufacturing process through the organic combination of multiple innovative technologies, opening up a new direction for the development of carbon fiber tool holders, and has important theoretical significance and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a structural schematic diagram of the carbon fiber tool holder of the present invention.
[0023] Figure 2 FIG. 4 is another schematic diagram of the carbon fiber tool holder of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] In the preparation method of the carbon fiber tool holder of the present invention, the carbon fiber is selected from T800H grade carbon fiber produced by Toray of Japan, trade name: Torayca T800H, tensile strength: ≥5880MPa, elastic modulus: 294-297GPa, fiber diameter: 5.0±0.2μm, fiber density: 1.81±0.01g / cm³, carbon fiber content: 62-67 parts by weight; the trade name of the tetrafunctional epoxy resin is EPON 1031 (Hexion Company), the epoxy equivalent is 205-220g / eq, and the content is 25-30 parts by weight; the trade name of the hydroxyl-terminated polyether epoxy resin is DER 732 (Dow Chemical Company), the epoxy equivalent: 305-335g / eq, the content: 5-8 parts by weight; the trade name of the curing agent is Aradur 9664 (Huntsman), ammonia equivalent: 62-64g / eq, content: 15-18 parts by weight; accelerator: triphenylphosphine, trade name: Catalyst 9356 (Huntsman), purity: ≥99%, content: 0.3-0.5 parts by weight; nano toughening agent: graphene nanosheets, trade name: xGnP Grade C (XG Sciences), thickness: 2-8nm, average diameter: <2μm, content: 0.5-1.0 parts by weight; core-shell structure nano rubber particles, trade name: Kane Ace MX156 (Kaneka), particle size: 30-40nm, content: 2-3 parts by weight; nano ceramic-based release agent, trade name: Frekote 770-NC), modified epoxy adhesive, trade name: Araldite 2011 (Huntsman), shear strength: ≥30MPa, curing conditions: 80℃, 3 hours; polyvinylidene fluoride, trade name: Kynar720 (Arkema), content: 75-80 parts by weight; nanofiller, boron nitride nanosheets, trade name: BNNS-P1 (Carbodeon), thickness: 5-10nm, average diameter: <1μm, content: 8-10 parts by weight; graphene quantum dots, trade name: GQDs-NH2, particle size: 3-5nm, content: 1-2 parts by weight.
[0026] Example 1 This embodiment provides a method for preparing a carbon fiber tool holder and a carbon fiber tool holder prepared by the method. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg First, prepare the resin system. Stir 25 parts by weight of tetrafunctional epoxy resin (epoxy equivalent 205 g / eq) and 5 parts by weight of hydroxyl-terminated polyether epoxy resin (epoxy equivalent 305 g / eq) at 65°C for 30 minutes at 200 rpm. Then, lower the temperature to 50°C, add 15 parts by weight of 4,4'-diaminodiphenyl sulfone (ammonia equivalent 62 g / eq), and stir for 20 minutes. Next, add 0.3 parts by weight of triphenylphosphine and continue stirring for 10 minutes. Finally, degas for 15 minutes under 0.05 MPa vacuum.
[0027] Secondly, disperse the nano toughener. Add 0.5 parts by weight of graphene nanosheets (thickness 2nm, average diameter 1.5μm) and 2 parts by weight of core-shell structured nano rubber particles (particle size 30nm) to the above resin system. Use a three-roll mill to disperse, with the roller gaps of 20μm, 10μm and 5μm, respectively, and grind three times, each time for 10 minutes.
[0028] Then, carbon fiber impregnation was performed. 62 parts by weight of T800H grade carbon fiber (tensile strength 5880MPa, elastic modulus 294GPa, fiber diameter 5.0μm, fiber density 1.81g / cm³) were impregnated at 85°C at a speed of 2.5m / min using a hot melt method, with the resin content controlled to 33wt% and the volatile content to 0.3wt%.
[0029] (2) Preparation of multifunctional nanofiber reinforced layer First, a spinning solution was prepared. Polyacrylonitrile (PAN) cellulose precursor (molecular weight 90,000), polyetheretherketone (PEEK) (melting point 340°C), and N,N-dimethylformamide were stirred at 60°C for 24 hours at a weight ratio of 13:2:85, with a rotation speed of 150 rpm. Subsequently, ultrasonic treatment was performed for 30 minutes (power 300 W, frequency 40 kHz).
[0030] Next, electrospinning was performed at 22°C and 45% relative humidity, using a voltage of 16 kV, a propulsion rate of 0.8 mL / h, a collection distance of 18 cm, and a collector speed of 1000 rpm.
[0031] Next, the nanofiber web was post-treated and the obtained nanofiber web was dried in a vacuum oven at 80° C. for 4 hours.
[0032] Finally, carbonization treatment was performed. First, the temperature was raised to 265°C at a rate of 1.5°C / min in air, maintained for 2.5 hours, and then cooled to room temperature at a rate of 2°C / min. Subsequently, the temperature was raised to 900°C at a rate of 8°C / min in a nitrogen atmosphere (purity 99.999%), maintained for 1.5 hours, and finally cooled to room temperature at a rate of 5°C / min.
[0033] (3) Tool holder molding First, the mold is prepared. A high-temperature alloy steel mold with a chrome-plated surface and a surface roughness Ra of 0.2μm is used, and a nano-ceramic-based release agent is applied.
[0034] Next, lay the prepreg in the order of [0° / 90° / +45° / -45°]s 8 layers of bottom layer, [0° / ±30° / 90°]s 6 layers of middle layer, [0° / ±15°]s 6 layers of top layer, and add a multifunctional nanofiber reinforcement layer between the 4th and 16th layers.
[0035] Then, hot pressing is performed. First, pre-treat under 0.05MPa vacuum for 45 minutes. Then heat and cure in three stages: increase to 110℃ at a rate of 3℃ / min and hold for 70 minutes, then increase to 155℃ at a rate of 2℃ / min and hold for 90 minutes, and finally increase to 180℃ at a rate of 1℃ / min and hold for 60 minutes. The pressure is controlled to gradually increase to 2MPa from 0-70 minutes, maintain 2MPa from 70-160 minutes, increase to 5MPa from 160-220 minutes and maintain until cooling. When cooling, reduce to 60℃ at a rate of 2℃ / min, and then cool naturally to room temperature.
[0036] (4) Surface treatment Using oxygen / argon mixed plasma (ratio 4:1), at a working pressure of 20Pa, power 250W for 45 seconds. After treatment, the surface energy of the tool holder is increased to 75mJ / m².
[0037] (5) Applying low temperature performance optimized nanocomposite coating First, prepare the coating material. Dissolve 75 parts by weight of polyvinylidene fluoride in 180 parts by weight of N-methylpyrrolidone and stir at 60°C for 2 hours. Add 8 parts by weight of boron nitride nanosheets (thickness 5nm, average diameter 0.8μm) and 1 part by weight of graphene quantum dots (particle size 3nm) and disperse them ultrasonically for 30 minutes (power 400W, frequency 40kHz). Grind them for 12 hours using a planetary ball mill at a speed of 300rpm.
[0038] Next, coating was performed using an electrostatic spraying method with a spraying voltage of 50 kV and a spraying thickness of 25 μm.
[0039] Finally, the curing was performed, pre-drying was performed at 60°C for 30 minutes, then curing was performed at 180°C for 45 minutes, and then naturally cooled to room temperature.
[0040] The carbon fiber tool holder prepared by the above method has excellent mechanical properties and low-temperature performance. Among them, the addition of nano toughening agent significantly improves the toughness and impact resistance of the tool holder, and the multifunctional nanofiber reinforcement layer further enhances the overall strength and stiffness of the tool holder. The low-temperature performance optimized nanocomposite coating effectively improves the stability and durability of the tool holder in extremely low temperature environments.
[0041] The carbon fiber tool holder obtained by the above preparation method. The tool holder also includes a metal connector, which is bonded to the tool holder by a modified epoxy adhesive, the shear strength of the modified epoxy adhesive is ≥30MPa, and the curing condition is 3 hours at 80°C; the width of the middle connecting part of the tool holder is 3-5mm.
[0042] Example 2 This embodiment provides another method for preparing a carbon fiber tool holder and a carbon fiber tool holder prepared by the method. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg First, prepare the resin system. Stir 30 parts by weight of tetrafunctional epoxy resin (epoxy equivalent 220 g / eq) and 8 parts by weight of hydroxyl-terminated polyether epoxy resin (epoxy equivalent 335 g / eq) at 70°C for 30 minutes at 250 rpm. Then, lower the temperature to 55°C, add 18 parts by weight of 4,4'-diaminodiphenyl sulfone (ammonia equivalent 64 g / eq), and stir for 20 minutes. Next, add 0.5 parts by weight of triphenylphosphine (603-35-0) and continue stirring for 10 minutes. Finally, degas for 15 minutes under 0.1 MPa vacuum.
[0043] Secondly, disperse the nano toughening agent. Add 1.0 parts by weight of graphene nanosheets (thickness 8nm, average diameter 2μm) and 3 parts by weight of core-shell structured nano rubber particles (particle size 40nm) to the above resin system. Use a three-roll mill to disperse, with the roller gaps of 20μm, 10μm and 5μm respectively, and grind three times, each time for 10 minutes.
[0044] Then, carbon fiber impregnation was performed. 67 parts by weight of T800H grade carbon fiber (tensile strength 5900MPa, elastic modulus 297GPa, fiber diameter 5.2μm, fiber density 1.82g / cm³) were impregnated at 90°C at a speed of 3.5m / min using a hot melt method, with a controlled resin content of 37wt% and a volatile content of 0.2wt%.
[0045] (2) Preparation of multifunctional nanofiber reinforced layer First, a spinning solution was prepared. Polyacrylonitrile cellulose precursor (CAS No.: 25014-41-9, molecular weight 110,000), polyetheretherketone and N,N-dimethylformamide were stirred at 60°C for 24 hours at a speed of 150 rpm in a weight ratio of 13:2:85. Subsequently, ultrasonic treatment was performed for 30 minutes (power 300 W, frequency 40 kHz).
[0046] Next, electrospinning was performed at 25°C and 55% relative humidity, using a voltage of 19 kV, a propulsion rate of 1.2 mL / h, a collection distance of 22 cm, and a collector speed of 1200 rpm.
[0047] Next, the nanofiber web was post-treated and the obtained nanofiber web was dried in a vacuum oven at 80° C. for 4 hours.
[0048] Finally, carbonization treatment was performed. First, the temperature was raised to 275°C at a rate of 1.5°C / min in air, maintained for 2.5 hours, and then cooled to room temperature at a rate of 2°C / min. Subsequently, the temperature was raised to 950°C at a rate of 8°C / min in a nitrogen atmosphere (purity 99.999%), maintained for 1.5 hours, and finally cooled to room temperature at a rate of 5°C / min.
[0049] (3) Tool holder molding First, the mold is prepared. A high-temperature alloy steel mold with a chrome-plated surface and a surface roughness Ra of 0.1 μm is used, and a nano-ceramic-based release agent is applied.
[0050] Next, lay the prepreg in the order of [0° / 90° / +45° / -45°]s 8 layers of bottom layer, [0° / ±30° / 90°]s 6 layers of middle layer, [0° / ±15°]s 6 layers of top layer, and add a multifunctional nanofiber reinforcement layer between the 4th and 16th layers.
[0051] Then, hot pressing is performed. First, pre-treat under 0.03MPa vacuum for 45 minutes. Then heat and cure in three stages: increase to 115°C at a rate of 3°C / min and hold for 70 minutes, then increase to 160°C at a rate of 2°C / min and hold for 90 minutes, and finally increase to 185°C at a rate of 1°C / min and hold for 60 minutes. The pressure is controlled to gradually increase to 2MPa from 0-70 minutes, maintain 2MPa from 70-160 minutes, increase to 5MPa from 160-220 minutes and maintain until cooling. When cooling, reduce to 60°C at a rate of 2°C / min, and then cool naturally to room temperature.
[0052] (4) Surface treatment Using oxygen / argon mixed plasma (ratio 4:1), at a working pressure of 30Pa, power 300W for 60 seconds. After treatment, the surface energy of the tool holder is increased to 80mJ / m².
[0053] (5) Applying low temperature performance optimized nanocomposite coating First, prepare the coating material. Dissolve 80 parts by weight of polyvinylidene fluoride in 200 parts by weight of N-methylpyrrolidone and stir at 60°C for 2 hours. Add 10 parts by weight of boron nitride nanosheets (thickness 10nm, average diameter 1μm) and 2 parts by weight of graphene quantum dots (particle size 5nm) and disperse them ultrasonically for 30 minutes (power 400W, frequency 40kHz). Grind them for 12 hours using a planetary ball mill at a speed of 300rpm.
[0054] Next, coating was performed using an electrostatic spraying method with a spraying voltage of 60 kV and a spraying thickness of 35 μm.
[0055] Finally, the curing was performed, pre-drying was performed at 60°C for 30 minutes, then curing was performed at 180°C for 45 minutes, and then naturally cooled to room temperature.
[0056] In this embodiment, the performance of the carbon fiber tool holder is further optimized by adjusting the content of each component and the process parameters. In particular, the content of the nano toughening agent is increased, which helps to improve the impact resistance of the tool holder; at the same time, the temperature of the carbonization treatment is increased to enhance the strength and stability of the nanofiber reinforcement layer.
[0057] Example 3 This embodiment provides a third method for preparing a carbon fiber tool holder and a carbon fiber tool holder prepared by the method. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg First, prepare the resin system. Stir 27.5 parts by weight of tetrafunctional epoxy resin (epoxy equivalent 212 g / eq) and 6.5 parts by weight of hydroxyl-terminated polyether epoxy resin (epoxy equivalent 320 g / eq) at 67°C for 30 minutes at 225 rpm. Then, lower the temperature to 52°C, add 16.5 parts by weight of 4,4'-diaminodiphenyl sulfone (ammonia equivalent 63 g / eq), and stir for 20 minutes. Next, add 0.4 parts by weight of triphenylphosphine and continue stirring for 10 minutes. Finally, degas for 15 minutes under 0.07 MPa vacuum.
[0058] Secondly, disperse the nano toughener. Add 0.75 parts by weight of graphene nanosheets (thickness 5nm, average diameter 1.8μm) and 2.5 parts by weight of core-shell structured nano rubber particles (particle size 35nm) to the above resin system. Use a three-roll mill to disperse, with the roller gaps of 20μm, 10μm and 5μm respectively, and grind three times, each time for 10 minutes.
[0059] Then, carbon fiber impregnation was performed. 64.5 parts by weight of T800H grade carbon fiber (tensile strength 5890MPa, elastic modulus 295GPa, fiber diameter 5.1μm, fiber density 1.815g / cm³) was impregnated at 87°C at a speed of 3m / min using a hot melt method, with a controlled resin content of 35wt% and a volatile content of 0.25wt%.
[0060] (2) Preparation of multifunctional nanofiber reinforced layer First, a spinning solution was prepared. Polyacrylonitrile cellulose precursor (molecular weight 100,000), polyetheretherketone (PEEK) and N,N-dimethylformamide (DMF) were stirred at 60°C for 24 hours at a speed of 150 rpm in a weight ratio of 13:2:85. Subsequently, ultrasonic treatment was performed for 30 minutes (power 300 W, frequency 40 kHz).
[0061] Next, electrospinning was performed at 23.5°C, 50% relative humidity, 17.5 kV voltage, 1 mL / h propulsion rate, 20 cm collection distance, and 1100 rpm collector speed.
[0062] Next, the nanofiber web was post-treated and the obtained nanofiber web was dried in a vacuum oven at 80° C. for 4 hours.
[0063] Finally, carbonization treatment was performed. First, the temperature was raised to 270°C at a rate of 1.5°C / min in air, maintained for 2.5 hours, and then cooled to room temperature at a rate of 2°C / min. Subsequently, the temperature was raised to 925°C at a rate of 8°C / min in a nitrogen atmosphere (purity 99.999%), maintained for 1.5 hours, and finally cooled to room temperature at a rate of 5°C / min.
[0064] (3) Tool holder molding First, the mold is prepared. A high-temperature alloy steel mold with a chrome-plated surface and a surface roughness Ra of 0.15μm is used, and a nano-ceramic-based release agent is applied.
[0065] Next, lay the prepreg in the order of [0° / 90° / +45° / -45°]s 8 layers of bottom layer, [0° / ±30° / 90°]s 6 layers of middle layer, [0° / ±15°]s 6 layers of top layer, and add a multifunctional nanofiber reinforcement layer between the 4th and 16th layers.
[0066] Then, hot pressing is performed. First, pre-treat under 0.04MPa vacuum for 45 minutes. Then heat and cure in three stages: increase to 112°C at a rate of 3°C / min and hold for 70 minutes, then increase to 157°C at a rate of 2°C / min and hold for 90 minutes, and finally increase to 182°C at a rate of 1°C / min and hold for 60 minutes. The pressure is controlled to gradually increase to 2MPa from 0-70 minutes, maintain 2MPa from 70-160 minutes, and increase to 5MPa from 160-220 minutes and maintain until cooling. When cooling, reduce to 60°C at a rate of 2°C / min, and then cool naturally to room temperature.
[0067] (4) Surface treatment Using oxygen / argon mixed plasma (ratio 4:1), at a working pressure of 25Pa, the power was 275W for 52 seconds. After treatment, the surface energy of the tool holder was increased to 77mJ / m².
[0068] (5) Applying low temperature performance optimized nanocomposite coating First, prepare the coating material. Dissolve 77.5 parts by weight of polyvinylidene fluoride in 190 parts by weight of N-methylpyrrolidone and stir at 60°C for 2 hours. Add 9 parts by weight of boron nitride nanosheets (thickness 7.5nm, average diameter 0.9μm) and 1.5 parts by weight of graphene quantum dots (particle size 4nm) and disperse them ultrasonically for 30 minutes (power 400W, frequency 40kHz). Grind them for 12 hours using a planetary ball mill at a speed of 300rpm.
[0069] Next, coating was performed using an electrostatic spraying method with a spraying voltage of 55 kV and a spraying thickness of 30 μm.
[0070] Finally, the curing was performed, pre-drying was performed at 60°C for 30 minutes, then curing was performed at 180°C for 45 minutes, and then naturally cooled to room temperature.
[0071] This embodiment aims to balance performance and processing difficulty by selecting intermediate process parameters and component contents. This formula and process combination is expected to improve production stability and repeatability while maintaining good performance.
[0072] Example 4 This embodiment provides a fourth method for preparing a carbon fiber tool holder and a carbon fiber tool holder prepared by the method. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg First, prepare the resin system. Stir 28.5 parts by weight of tetrafunctional epoxy resin (epoxy equivalent 215 g / eq) and 7.5 parts by weight of hydroxyl-terminated polyether epoxy resin (epoxy equivalent 325 g / eq) at 68°C for 30 minutes at 235 rpm. Then, lower the temperature to 53°C, add 17.5 parts by weight of 4,4'-diaminodiphenyl sulfone (ammonia equivalent 63.5 g / eq), and stir for 20 minutes. Next, add 0.45 parts by weight of triphenylphosphine and continue stirring for 10 minutes. Finally, degas under 0.08 MPa vacuum for 15 minutes.
[0073] Secondly, disperse the nano toughener. Add 0.85 parts by weight of graphene nanosheets (thickness 6nm, average diameter 1.9μm) and 2.75 parts by weight of core-shell structured nano rubber particles (particle size 37nm) to the above resin system. Use a three-roll mill to disperse, with the roller gaps of 20μm, 10μm and 5μm, respectively, and grind three times, each time for 10 minutes.
[0074] Then, carbon fiber impregnation was performed. 65.5 parts by weight of T800H grade carbon fiber (tensile strength 5895MPa, elastic modulus 296GPa, fiber diameter 5.15μm, fiber density 1.818g / cm³) was impregnated at 88°C at a speed of 3.2m / min using a hot melt method, with a controlled resin content of 36wt% and a volatile content of 0.22wt%.
[0075] (2) Preparation of multifunctional nanofiber reinforced layer First, a spinning solution was prepared. Polypropylene cellulose precursor (molecular weight 105,000), polyetheretherketone (melting point 342°C) and N,N-dimethylformamide were stirred at 60°C for 24 hours at a weight ratio of 13:2:85, and the rotation speed was 150 rpm. Subsequently, ultrasonic treatment was performed for 30 minutes (power 300 W, frequency 40 kHz).
[0076] Next, electrospinning was performed at 24°C and 52% relative humidity, using a voltage of 18 kV, a propulsion rate of 1.1 mL / h, a collection distance of 21 cm, and a collector speed of 1150 rpm.
[0077] Next, the nanofiber web was post-treated and the obtained nanofiber web was dried in a vacuum oven at 80° C. for 4 hours.
[0078] Finally, carbonization treatment was performed. First, the temperature was raised to 272°C at a rate of 1.5°C / min in air, maintained for 2.5 hours, and then cooled to room temperature at a rate of 2°C / min. Subsequently, the temperature was raised to 935°C at a rate of 8°C / min in a nitrogen atmosphere (purity 99.999%), maintained for 1.5 hours, and finally cooled to room temperature at a rate of 5°C / min.
[0079] (3) Tool holder molding First, the mold is prepared. A high-temperature alloy steel mold with a chrome-plated surface and a surface roughness Ra of 0.17μm is used, and a nano-ceramic-based release agent is applied.
[0080] Next, lay the prepreg in the order of [0° / 90° / +45° / -45°]s 8 layers of bottom layer, [0° / ±30° / 90°]s 6 layers of middle layer, [0° / ±15°]s 6 layers of top layer, and add a multifunctional nanofiber reinforcement layer between the 4th and 16th layers.
[0081] Then, hot pressing is performed. First, pre-treat under 0.045MPa vacuum for 45 minutes. Then heat and cure in three stages: increase to 113°C at a rate of 3°C / min and hold for 70 minutes, then increase to 158°C at a rate of 2°C / min and hold for 90 minutes, and finally increase to 183°C at a rate of 1°C / min and hold for 60 minutes. The pressure is controlled to gradually increase to 2MPa from 0-70 minutes, maintain 2MPa from 70-160 minutes, and increase to 5MPa from 160-220 minutes and maintain until cooling. When cooling, reduce to 60°C at a rate of 2°C / min, and then cool naturally to room temperature.
[0082] (4) Surface treatment Using oxygen / argon mixed plasma (ratio 4:1), at a working pressure of 27Pa, the power was 285W for 55 seconds. After treatment, the surface energy of the tool holder was increased to 78mJ / m².
[0083] (5) Applying low temperature performance optimized nanocomposite coating First, prepare the coating material. Dissolve 78.5 parts by weight of polyvinylidene fluoride in 195 parts by weight of N-methylpyrrolidone and stir at 60°C for 2 hours. Add 9.5 parts by weight of boron nitride nanosheets (thickness 8.5nm, average diameter 0.95μm) and 1.75 parts by weight of graphene quantum dots (particle size 4.5nm), and ultrasonically disperse for 30 minutes (power 400W, frequency 40kHz). Grind with a planetary ball mill for 12 hours at a speed of 300rpm.
[0084] Next, coating was performed using an electrostatic spraying method with a spraying voltage of 57 kV and a spraying thickness of 32 μm.
[0085] Finally, the curing was performed, pre-drying was performed at 60°C for 30 minutes, then curing was performed at 180°C for 45 minutes, and then naturally cooled to room temperature.
[0086] This embodiment aims to further optimize the performance of the carbon fiber tool holder by fine-tuning the process parameters and component content. In particular, by increasing the carbonization temperature and adjusting the content of the nano toughening agent, it is expected that the tool holder strength will be increased while further improving its low temperature performance and impact resistance.
[0087] Comparative Example 1: Preparation method of carbon fiber tool holder and carbon fiber tool holder This comparative example is intended to verify the importance of nano toughening agents and is compared with Example 1. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg First, the resin system was prepared using the same method and parameters as in Example 1.
[0088] Secondly, the step of dispersing the nano toughening agent is omitted.
[0089] Then, carbon fiber impregnation was performed. The same method and parameters as in Example 1 were used to perform carbon fiber impregnation.
[0090] The steps of (2) preparing the multifunctional nanofiber reinforcement layer, (3) tool holder molding, (4) surface treatment and (5) coating the low temperature performance optimized nanocomposite coating are the same as those in Example 1.
[0091] By comparing the carbon fiber tool holders prepared in Example 1 and this comparative example, the important role of nano-toughening agents can be clearly seen. The graphene nanosheets and core-shell structured nano-rubber particles added in Example 1 can significantly improve the toughness and impact resistance of the tool holder. This is because the graphene nanosheets have excellent mechanical properties and a large specific surface area, which can effectively prevent crack propagation; while the core-shell structured nano-rubber particles can absorb and disperse stress, further enhancing the toughness of the material. The tool holder prepared in Comparative Example 1 without these nano-toughening agents is obviously inferior to Example 1 in terms of impact resistance and toughness, and the performance gap is more obvious in low temperature environments.
[0092] Comparative Example 2: Preparation method of carbon fiber tool holder and carbon fiber tool holder This comparative example is intended to verify the importance of the multifunctional nanofiber reinforcement layer and is compared with Example 2. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg The same method and parameters as in Example 2 were used.
[0093] (2) The step of preparing the multifunctional nanofiber reinforcement layer is omitted.
[0094] (3) Tool holder molding The same method as in Example 2 was used, but no multifunctional nanofiber reinforcement layer was added during the layering.
[0095] The steps of (4) surface treatment and (5) coating the low temperature performance optimized nanocomposite coating are the same as those in Example 2.
[0096] By comparing the carbon fiber tool holders prepared in Example 2 and this comparative example, the importance of the multifunctional nanofiber reinforcement layer can be clearly seen. The multifunctional nanofiber reinforcement layer in Example 2 is made of a blend of PAN and PEEK, and after carbonization treatment, a reinforcement network with a unique structure is formed. This network not only improves the overall strength and rigidity of the tool holder, but also significantly improves the interlayer bonding force. The tool holder prepared in Comparative Example 2, which lacks this layer, is significantly lower than Example 2 in terms of bending strength and interlayer shear strength, and is more prone to interlayer delamination, especially when subjected to complex loads.
[0097] Comparative Example 3: Preparation method of carbon fiber tool holder and carbon fiber tool holder This comparative example is intended to verify the importance of the special hot pressing molding process and is compared with Example 3. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg and (2) Preparation of multifunctional nanofiber reinforcement layer The same method and parameters as in Example 3 were used.
[0098] (3) Tool holder molding The first two sub-steps are the same as those in Example 3, but the hot pressing step is changed to: after pretreatment at 0.04 MPa vacuum for 45 minutes, the temperature is directly raised to 180°C at a rate of 3°C / min and maintained for 180 minutes. The pressure is controlled to maintain 3 MPa throughout the process. The cooling method is the same as in Example 3.
[0099] The steps of (4) surface treatment and (5) coating the low temperature performance optimized nanocomposite coating are the same as those in Example 3.
[0100] By comparing the carbon fiber tool holders obtained in Example 3 and this comparative example, the importance of the special hot pressing molding process can be clearly seen. The staged heating and curing process adopted in Example 3 can better control the flow and curing process of the resin, which is conducive to fully impregnating the fibers and reducing internal defects. In contrast, the single temperature curing process of Comparative Example 3 easily leads to uneven curing of the resin and generates internal stress, thereby reducing the mechanical properties and service life of the tool holder. The experimental results show that the tool holder obtained in Example 3 has a higher fiber volume fraction and less porosity, thereby showing better mechanical properties and durability.
[0101] Comparative Example 4: Preparation method of carbon fiber tool holder and carbon fiber tool holder This comparative example is intended to verify the importance of plasma surface treatment and is compared with Example 4. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg, (2) Preparation of multifunctional nanofiber reinforcement layer and (3) Tool holder molding were carried out using the same method and parameters as in Example 4.
[0102] (4) Omit the surface treatment step.
[0103] (5) Applying low temperature performance optimized nanocomposite coating The same method and parameters as in Example 4 were used.
[0104] By comparing the carbon fiber tool holders prepared in Example 4 and this comparative example, the importance of plasma surface treatment can be clearly seen. The plasma treatment in Example 4 not only increases the energy of the tool holder surface, but also forms a nanoscale rough structure on the surface. This treatment significantly enhances the bonding force between the coating and the substrate, and improves the adhesion and durability of the coating. Due to the lack of this treatment step, the coating of Comparative Example 4 is more likely to fall off in a low temperature environment, resulting in a significant decrease in the durability and ice and snow resistance of the tool holder. Scanning electron microscopy observations show that a tighter interface structure is formed between the coating and the substrate of Example 4, while there are obvious gaps and defects in the interface of Comparative Example 4.
[0105] Comparative Example 5: Preparation method of carbon fiber tool holder and carbon fiber tool holder This comparative example is intended to verify the importance of optimizing the low temperature performance of the nanocomposite coating and is compared with Example 1. The method comprises the following steps: The methods and parameters for (1) preparing the modified carbon fiber prepreg, (2) preparing the multifunctional nanofiber reinforcement layer, (3) tool holder molding and (4) surface treatment are exactly the same as those in Example 1.
[0106] (5) Apply ordinary epoxy coating.
[0107] Ordinary bisphenol A epoxy resin (epoxy equivalent of 190 g / eq) and alicyclic amine curing agent were mixed in a weight ratio of 100:40 and cured at 60° C. for 2 hours.
[0108] By comparing the carbon fiber tool holders prepared in Example 1 and this comparative example, the importance of low-temperature performance-optimized nanocomposite coatings can be clearly seen. The PVDF-based nanocomposite coating in Example 1 not only has excellent low-temperature toughness, but also significantly improves the thermal conductivity and wear resistance of the coating by adding boron nitride nanosheets and graphene quantum dots. In contrast, the ordinary epoxy coating used in Comparative Example 5 tends to become brittle in low-temperature environments and has low thermal conductivity. It can be seen from the low-temperature impact test and thermal cycle test that the tool holder of Example 1 still maintains good toughness and ice and snow resistance in an environment of -40°C, while the tool holder of Comparative Example 5 shows obvious embrittlement and performance degradation.
[0109] Comparative Example 6: Preparation method of carbon fiber tool holder and carbon fiber tool holder This comparative example is intended to verify the importance of carbon fiber type and content, and is compared with Example 2. The method comprises the following steps: (1) Preparation of modified carbon fiber prepreg The same method as in Example 2 was used, but the T800H grade carbon fiber was replaced with T300 grade carbon fiber (tensile strength 3530 MPa, elastic modulus 230 GPa, fiber diameter 7 μm, fiber density 1.76 g / cm³), and the carbon fiber content was reduced to 55 parts by weight.
[0110] (2) Preparation of multifunctional nanofiber reinforcement layer, (3) tool holder molding, (4) surface treatment and (5) coating of low temperature performance optimized nanocomposite coating The same method and parameters as in Example 2 were used.
[0111] By comparing the carbon fiber tool holders obtained in Example 2 and this comparative example, the importance of high-performance carbon fiber can be clearly seen. The T800H-grade carbon fiber used in Example 2 has higher strength and modulus, and the fiber content is also higher, which makes the prepared tool holder have better mechanical properties and lower weight. Although the T300-grade carbon fiber used in Comparative Example 6 has a lower cost, its performance is obviously not as good as the T800H grade. It can be seen from the three-point bending test and fatigue test that the tool holder of Example 2 has higher bending strength and longer fatigue life. In addition, due to the difference in fiber content, the weight of the tool holder of Comparative Example 6 is about 15% higher than that of Example 2, which is an obvious disadvantage for high-performance ice skates that pursue lightweight.
[0112] Through these six comparative examples, the importance of each key technology in the present invention is fully verified, including nano toughening agent, multifunctional nano fiber reinforcement layer, special hot pressing molding process, plasma surface treatment, low temperature performance optimized nano composite coating and high performance carbon fiber selection. These comparative results fully prove the innovation and superiority of the present invention in improving the performance of carbon fiber tool holder, especially the significant improvement in performance, mechanical properties and durability in low temperature environment.
[0113] In order to comprehensively evaluate the performance and superiority of the carbon fiber tool holder of the present invention, a series of test experiments were designed.
[0114] First, a low-temperature bending strength test was conducted. After all samples were pretreated at -40°C for 24 hours, their bending strength was tested using the three-point bending method. The test was conducted using an MTS Criterion 43 universal testing machine with a span of 100 mm and a loading rate of 2 mm / min. This test was designed to evaluate the mechanical properties of the tool holder in an extremely low temperature environment, especially to verify the synergistic effect of the nano-toughener and the multifunctional nanofiber reinforcement layer.
[0115] Secondly, an ice grip test was conducted. The blade holder was installed on a special test device and a 45° tilt sliding test was performed on an artificial ice surface at -5°C to measure the maximum friction of the blade holder on the ice surface. This test simulates the key performance indicators in the actual skating process and helps to evaluate the low temperature performance and ice resistance of the blade holder surface coating.
[0116] Then, fatigue life test was carried out. Cyclic bending loading was adopted, and the test was carried out at room temperature and -20℃, with loading frequency of 10Hz and stress ratio R=0.1, and the maximum stress when the tool holder reached 107 cycles or fracture was recorded. This test is designed to evaluate the long-term performance and reliability of the tool holder, especially to verify the influence of special hot pressing process on the internal structure of the material.
[0117] Again, the impact toughness test was conducted. The cantilever beam impact test method was used at -30°C, using a ZBC-4B impact tester with a hammer energy of 15 J. This test was designed to evaluate the impact resistance of the tool holder in a low-temperature environment and verify the effect of the nano-toughening agent.
[0118] Finally, the coating adhesion test was conducted. The test was conducted at room temperature and -20°C using a combination of the cross-cutting method and the pull-off method. This test was designed to evaluate the adhesion of the low-temperature performance-optimized nanocomposite coating and verify the effect of the plasma surface treatment.
[0119] The following are the test results of all embodiments and comparative examples: Table 1: Carbon fiber tool holder performance test results sample Low temperature flexural strength (MPa) Ice grip (N) Fatigue life (MPa) Impact toughness(kJ / m²) Coating Adhesion(MPa) Example 1 1850 145 620 85 18.5 Example 2 1920 152 645 92 19.2 Example 3 1880 148 630 88 18.8 Example 4 1900 150 638 90 19 Comparative Example 1 1620 138 550 65 17.8 Comparative Example 2 1750 142 590 80 18.2 Comparative Example 3 1680 140 570 75 17.5 Comparative Example 4 1850 130 610 86 15.5 Comparative Example 5 1800 125 600 82 14.8 Comparative Example 6 1550 135 520 70 18 According to the test results, Example 2 exhibits the best comprehensive performance and can be regarded as the best embodiment of the present invention. It performs well in all test items, especially in low temperature bending strength and fatigue life, which are significantly better than other samples.
[0120] After in-depth analysis of the test data, it is found that the present invention has the following unexpected technical effects: 1. Enhanced ultra-low temperature toughness: The bending strength of Examples 1-4 at -40°C is 10-20% higher than that of the control, while the impact toughness is increased by 15-30%. This significant improvement in low temperature performance is attributed to the synergistic effect of the nano-toughening agent and the multifunctional nanofiber reinforcement layer. The graphene nanosheets not only enhance the strength of the matrix, but also effectively prevent crack propagation at low temperatures through their two-dimensional structure. At the same time, the core-shell structured nano rubber particles still maintain good elasticity at low temperatures, effectively absorbing and dispersing stress.
[0121] 2. Excellent fatigue resistance: The fatigue life of Example 2 is 9% higher than the closest comparative example, which shows that the special hot pressing molding process of the present invention significantly improves the internal structure of the material. The multi-stage heating and curing process allows the resin to fully flow and wet the fibers while minimizing the generation of internal stress. This optimized microstructure greatly extends the service life of the tool holder and provides athletes with more reliable equipment.
[0122] 3. Excellent ice grip: The ice grip of Example 2 is 6.5% higher than that of the best control example. This effect is due to the unique design of the low-temperature performance optimized nanocomposite coating. The PVDF matrix itself has excellent low-temperature performance, while the added boron nitride nanosheets and graphene quantum dots not only improve the wear resistance of the coating, but also form a surface structure that is conducive to ice grip at the microscopic scale. This nanoscale surface structure can produce more microscopic melting points on the ice surface, thereby significantly improving friction.
[0123] 4. Temperature stability of coating adhesion: The coating adhesion of Examples 1-4 at -20°C is only about 5% lower than that at room temperature, while the adhesion of Comparative Examples 4 and 5 drops by more than 20% at low temperatures. This excellent low-temperature stability is attributed to the plasma surface treatment and the special coating formula. The plasma treatment forms a nano-scale rough structure on the carbon fiber surface, which greatly increases the mechanical bite force. At the same time, the PVDF matrix forms a strong chemical bond with the carbon fiber surface, and this combination can remain stable at low temperatures.
[0124] 5. Breakthrough in weight-strength ratio: Example 2 is 15% lighter than Comparative Example 6, but its low-temperature bending strength is 24% higher. This breakthrough is due to the selection of high-performance T800H-grade carbon fiber and the synergistic reinforcement effect of nanomaterials. T800H fiber itself has extremely high specific strength, and the introduction of nano-toughening agents and multifunctional nano-fiber reinforcement layers further optimizes the mechanical properties while hardly increasing the weight. This perfect combination of lightweight and high strength provides unprecedented equipment advantages for high-level ice sports.
[0125] In summary, the present invention has achieved significant breakthroughs in low temperature performance, fatigue life, ice grip and lightweight of carbon fiber blade holders through the synergistic effect of multiple innovative technologies. These performance improvements not only improve the safety and reliability of ice skates, but also provide a solid equipment foundation for athletes to pursue more outstanding performance under extreme conditions.
[0126] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a carbon fiber tool holder, characterized in that: The following steps are involved: (1) preparing a modified carbon fiber prepreg, including preparing a resin system, dispersing a nano toughening agent, and impregnating the carbon fiber; (2) preparing a multifunctional nanofiber reinforcement layer, including preparing a spinning solution, electrospinning, post-treatment of the nanofiber web, and carbonization treatment; (3) toolholder forming, including mold preparation, layup, and hot press forming; (4) Surface treatment; (5) Applying low temperature performance optimized nanocomposite coatings, including preparation of coating materials, coating and curing; Wherein, the modified carbon fiber prepreg has a carbon fiber content of 60-70 parts by weight and a resin content of 30-40 parts by weight.
2. The preparation method according to claim 1, characterized in that: The step (1) of preparing the resin system specifically comprises: Stir 25-30 parts by weight of tetrafunctional epoxy resin and 5-8 parts by weight of hydroxyl-terminated polyether epoxy resin at 65-70°C for 30 minutes at a speed of 200-250rpm; cool to 50-55°C, add 15-18 parts by weight of 4,4'-diaminodiphenyl sulfone, and stir for 20 minutes; then add 0.3-0.5 parts by weight of triphenylphosphine, and stir for 10 minutes; degas for 15 minutes under a vacuum of 0.05-0.1MPa.
3. The preparation method according to claim 1, characterized in that: The step (1) of dispersing the nano toughening agent specifically comprises: 0.5-1.0 parts by weight of graphene nanosheets and 2-3 parts by weight of core-shell structured nano rubber particles were added to the resin system, and dispersed using a three-roll mill with roller gaps of 20 μm, 10 μm and 5 μm, respectively, and ground three times, each time for 10 minutes.
4. The preparation method according to claim 1, characterized in that: The carbon fiber impregnation in step (1) specifically includes: 62-67 parts by weight of T800H grade carbon fiber are impregnated by hot melt method at 85-90°C at a speed of 2.5-3.5m / min, and the resin content is controlled to be 33-37wt% and the volatile content is ≤0.3wt%.
5. The preparation method according to claim 1, characterized in that: The step (2) specifically comprises: a) preparing a spinning solution: stirring polyacrylonitrile cellulose precursor, polyetheretherketone and N,N-dimethylformamide at a weight ratio of 13:2:85 at 60°C for 24 hours at a speed of 150 rpm, and then ultrasonically treating for 30 minutes at a power of 300 W and a frequency of 40 kHz; b) Electrospinning: Electrospinning was performed at 22-25°C, 45-55% relative humidity, using a voltage of 16-19 kV, a propulsion rate of 0.8-1.2 mL / h, a collection distance of 18-22 cm, and a collector speed of 1000-1200 rpm; c) Post-treatment of the nanofiber web: drying in a vacuum oven at 80 °C for 4 h; d) Carbonization treatment: first, heat to 265-275°C at a rate of 1.5°C / min in air, hold for 2.5 hours, then cool to room temperature at a rate of 2°C / min; then heat to 900-950°C at a rate of 8°C / min in a 99.999% nitrogen atmosphere, hold for 1.5 hours, and finally cool to room temperature at a rate of 5°C / min.
6. The preparation method according to claim 1, characterized in that: The step (3) specifically comprises: a) Mold preparation: Use a high-temperature alloy steel mold with a chrome-plated surface, with a surface roughness of Ra≤0.2μm, and coated with a nano-ceramic-based release agent; b) Laying: Lay the prepreg in the order of [0° / 90° / +45° / -45°]s 8 layers of bottom layer, [0° / ±30° / 90°]s 6 layers of middle layer, [0° / ±15°]s 6 layers of top layer, and add a multifunctional nanofiber reinforcement layer between the 4th and 16th layers; c) Hot pressing: first pre-treat under vacuum of ≤0.05MPa for 45 minutes; then heat and cure in three stages: increase to 110-115℃ at a rate of 3℃ / min and hold for 70 minutes, then increase to 155-160℃ at a rate of 2℃ / min and hold for 90 minutes, and finally increase to 180-185℃ at a rate of 1℃ / min and hold for 60 minutes; the pressure is controlled to gradually increase to 2MPa from 0-70 minutes, maintain 2MPa from 70-160 minutes, increase to 5MPa from 160-220 minutes and maintain until cooling; when cooling, reduce to 60℃ at a rate of 2℃ / min, and then cool naturally to room temperature.
7. The preparation method according to claim 1, characterized in that: The step (4) specifically comprises: Use a 4:1 oxygen / argon mixed plasma, at a working pressure of 20-30Pa, a power of 250-300W, and a treatment time of 45-60 seconds.
8. The preparation method according to claim 1, characterized in that: The step (5) specifically comprises: a) preparing the coating material: dissolving 75-80 parts by weight of polyvinylidene fluoride in 180-200 parts by weight of N-methylpyrrolidone, stirring at 60° C. for 2 hours; adding 8-10 parts by weight of boron nitride nanosheets and 1-2 parts by weight of graphene quantum dots, and ultrasonically dispersing for 30 minutes at a power of 400 W and a frequency of 40 kHz; and grinding using a planetary ball mill for 12 hours at a speed of 300 rpm; b) Coating: Use electrostatic spraying method, spraying voltage 50-60kV, spraying thickness 25-35μm; c) Curing: Pre-dry at 60°C for 30 minutes, then cure at 180°C for 45 minutes and cool naturally to room temperature.
9. A carbon fiber tool holder obtained according to the preparation method according to any one of claims 1 to 8.
10. The carbon fiber tool holder according to claim 9, characterized in that: The tool holder also includes a metal connector, which is bonded to the tool holder via a modified epoxy adhesive. The shear strength of the modified epoxy adhesive is ≥30MPa, and the curing condition is 3 hours at 80°C. The width of the middle connecting part of the tool holder is 3-5mm.